Na investigation of previous athletes (Fiep Bulletin - online, 2015)
At the commencement of this century there were approximately 50,000 active athletes in Denmark and, today, there are about one million. More than 200 million Danish crowns (10 million Pounds) are expended annually by the Danish state, municipalities and private enterprises, to sport.